Characterisation of carotid atheroma in symptomatic and asymptomatic patients using high resolution MRI. Issue 8 (10th January 2008) - U-King-Im, J M; Tang, T Y; Patterson, A; Graves, M J; Howarth, S; Li, Z-Y; Trivedi, R; Bowden, D; Kirkpatrick, P J; Gaunt, M E; Warburton, E A; Antoun, N M; et al.
Abstract : Background and purpose: To prospectively evaluate differences in carotid plaque characteristics in symptomatic and asymptomatic patients using high resolution MRI. Methods: 20 symptomatic and 20 asymptomatic patients, with at least 50% carotid stenosis as determined by Doppler ultrasound, underwent preoperative in vivo multispectral MRI of the carotid arteries. Studies were analysed both qualitatively and quantitatively in a randomised manner by two experienced readers in consensus, blinded to clinical status, and plaques were classified according to the modified American Heart Association (AHA) criteria. Results: After exclusion of poor quality images, 109 MRI sections in 18 symptomatic and 19 asymptomatic patients were available for analysis. There were no significant differences in mean luminal stenosis severity (72.9% vs 67.6%; p = 0.09) or plaque burden (median plaque areas 50 mm 2 vs 50 mm 2 ; p = 0.858) between the symptomatic and asymptomatic groups. However, symptomatic lesions had a higher incidence of ruptured fibrous caps (36.5% vs 8.7%; p = 0.004), haemorrhage or thrombus (46.5% vs 14.0%; p<0.001), large necrotic lipid cores (63.8% vs 28.0%; p = 0.002) and complicated type VI AHA lesions (61.5% vs 28.1%; p = 0.001) compared with asymptomatic lesions. The MRI findings of plaque haemorrhage or thrombus had an odds ratio of 5.25 (95% CI 2.08 to 13.24) while thin or ruptured fibrous cap (as opposed to a thick fibrous cap) had an odds ratio of 7.94 (95% CI 2.93 to 21.51) for prediction of symptomatic clinical status. Conclusions: There are significant differences in plaque characteristics between symptomatic and asymptomatic carotid atheroma and these can be detected in vivo by high resolution MRI.